Observation of electroweak production of two jets in association with an isolated photon and missing transverse momentum, and search for a Higgs boson decaying into invisible particles at 13 TeV with the ATLAS detector - Aad, G.; Abbott, B.; Abbott, D. C.; Aliev, M.; Kostyukhin, Vadim V.; Kuchinskaya, Olesya I.; Penzin, Maxim S. (The European physical journal C)
This paper presents a measurement of the electroweak production of two jets in association with a Z gamma pair, with the Z boson decaying into two neutrinos. It also presents a search for invisible or partially invisible decays of a Higgs boson with a mass of 125 GeV produced through vectorboson fusion with a photon in the final state. These results use data from LHC proton-proton collisions at root s = 13 TeV collected with the ATLAS detector and corresponding to an integated luminosity of 139 fb(-1). The event signature, shared by all benchmark processes considered for the measurements and searches, is characterized by a significant amount of unbalanced transverse momentum and a photon in the final state, in addition to a pair of forward jets. Electroweak Z gamma production in association with two jets is observed in this final state with a significance of 5.2 (5.1 expected) standard deviations. The measured fiducial cross-section for this process is 1.31 +/- 0.29 fb. An observed (expected) upper limit of 0.37 (0.34(-0.10)(+0.15)) at 95% confidence level is set on the branching ratio of a 125 GeV Higgs boson to invisible particles, assuming the Standard Model production cross-section. The signature is also interpreted in the context of decays of a Higgs boson into a photon and a dark photon. An observed (expected) 95% CL upper limit on the branching ratio for this decay is set at 0.018 (0.017(-0.005)(+0.007)), assuming the Standard Model production cross-section for a 125 GeV Higgs boson.